Sales and Operations Planning: Augmenting Existing Maturity Models with New Practices - Nyman, Henrik J.; Tschirch, Fabian (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Sales and Operations Planning (S&OP) is a vital mechanism for aligning operations with financial objectives. Despite its importance, traditional S&OP maturity models often lag behind advancements in data science, resulting in a "digital blind spot" for companies implementing S&OP. This paper investigates how existing maturity models should be complemented to incorporate recent advances in data science. We arrived at our results by first synthesizing five prominent maturity models into four core dimensions: process, people and organization, performance management, and IT and data. We then conducted a systematic literature review of 24 articles, detailing how emerging technologies affect S&OP maturity in these four dimensions. Ultimately, this research provides key considerations for aligning S&OP excellence with modern technological capabilities.